Transition States of Plasmodium falciparum and Human Orotate Phosphoribosyltransferases - Zhang, Yong (2009)
Orotate phosphoribosyltransferases (OPRT) catalyze the formation of orotidine 5′-monophosphate (OMP) from α-D-phosphoribosylpyrophosphate (PRPP) and orotate, an essential step in the de novo biosynthesis of pyrimidines. Pyrimidine de novo biosynthesis is required in Plasmodium falciparum, thus OPRT of the parasite (PfOPRT) is a target for anti-malarial drugs. De novo biosynthesis of pyrimidines is also a feature of rapidly-proliferating cancer cells. Human OPRT (HsOPRT) is therefore a target for neoplastic and autoimmune diseases. One approach to the inhibition of OPRTs is through analogues that mimic the transition states of PfOPRT and HsOPRT. The transition state structures of these OPRTs were analyzed by kinetic isotope effects (KIEs), substrate specificity and computational chemistry. With phosphonoacetic acid (PA), an analogue of pyrophosphate, the intrinsic KIEs of [1′-(14)C], [1, 3-(15)N(2)], [3-(15)N], [1′-(3)H], [2′-(3)H], [4′-(3)H] and [5′-(3)H(2)] are 1.034, 1.028, 0.997, 1.261, 1.116, 0.974 and 1.013 for PfOPRT and 1.035, 1.025, 0.993, 1.199, 1.129, 0.962 and 1.019 for HsOPRT, respectively. Transition state structures of PfOPRT and HsOPRT were determined computationally by matching the calculated and intrinsic KIEs. The enzymes form late associative D(N)*A(N)(‡) transition states with complete orotate loss and partially-associative nucleophile. The C1′-O(PA) distances are approximately 2.1 Å at these transition states. The modest [1′-(14)C] KIEs and large [1′-(3)H] KIEs are characteristic of D(N)*A(N)(‡) transition states. The large [2′-(3)H] KIEs indicate a ribosyl 2′-C-endo conformation at the transition states. p-Nitrophenyl β-Dribose 5′-phosphate is a poor substrate of PfOPRT and HsOPRT but is a nanomolar inhibitor, supporting a reaction coordinate with strong leaving group activation.